Updating Public Legal Awareness of Restricting Carbon Emissions in Indonesia - Andreas Tedy Mulyono; Rudy Pramono (Law Review, 2022)
The Government of Indonesia will impose restrictions on carbon emissions. The description of public legal awareness regarding this matter is currently an important aspect as one of the benchmarks, especially for updating the status of carbon emission regulations in Indonesian society. This literature study focuses on the importance and use of empirical quantitative research methods based on questionnaire data from respondents in various regions in Indonesia. The discussion using the Regulatory Status Analysis (RSA) path model assisted by the PLS-SEM software specifically provides an understanding of the relationship between the ideal Law and legal culture in the form of public awareness to comply with legal norms limiting carbon emissions. Another element of the legal system, namely the substance of the Law, also has a positive effect on awareness of obeying the Law. However, the legal Structure has no effect, either directly or indirectly. The possible reason is that the legal Structure, the indicator of which is law enforcement related to carbon emission cases, has not been widely processed in domestic courts in Indonesia. This study also conducts an intersubjective meaning approach by interviewing related entrepreneurs to strengthen statistical inferences. The article concludes by placing these findings in the discourse on limiting national carbon emissions based on political will and participatory governance.